2014
DOI: 10.1149/2.0031503jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Covalency on the Mn4+ 2Eg4A2gEmission Energy in Crystals

Abstract: In this paper we review the spectroscopic properties of the Mn4+ ion (3d electronic configuration) and establish a relationship between the energy of the 2Eg → 4A2g emission transition and the covalence of the “Mn4+-ligand” bonding. A new parameter β1=(normalBB0)2+(normalCC0)2 (where (B, C (B0, C0) are the Racah parameters of the Mn4+ ions in a crystal (free state), respectively) was recently introduced that allows for establishing a linear relationship between β1 and the energy of the 2Eg level. This makes it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
194
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(216 citation statements)
references
References 44 publications
(23 reference statements)
12
194
1
Order By: Relevance
“…For example, based on the spectroscopic properties of the Mn 4+ ion, Brik and Srivastava observed that the emission wavelength of Mn 4+ generally increases with the increasing covalency of the Mn-ligand bonds. 36,37 Density functional theory (DFT) calculations of Mn 4+ emission in a large number of oxides and fluorides revealed the influence of the local structures to the activator-ligand hybridization strength and the emission energies. 38,39 These insights are very useful for searching for new Mn 4+ -activated red phosphors.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (1) R30mentioning
confidence: 99%
“…For example, based on the spectroscopic properties of the Mn 4+ ion, Brik and Srivastava observed that the emission wavelength of Mn 4+ generally increases with the increasing covalency of the Mn-ligand bonds. 36,37 Density functional theory (DFT) calculations of Mn 4+ emission in a large number of oxides and fluorides revealed the influence of the local structures to the activator-ligand hybridization strength and the emission energies. 38,39 These insights are very useful for searching for new Mn 4+ -activated red phosphors.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (1) R30mentioning
confidence: 99%
“…Investigation of the optical properties of the Mn 4+ dopant showed that fluoride hosts are preferred for LED phosphors over oxide hosts, since only the ionic nature of fluorides results in a sufficiently small nephelauxetic effect, maintaining the energy of the emitting 2 E g → 4 A 2g transition within the visible part of the spectrum, corresponding to red emission with a zero phonon line in the 617-624 nm range. 8,9 For instance in the oxide phosphors, …”
mentioning
confidence: 99%
“…Investigation of the optical properties of the Mn 4+ dopant showed that fluoride hosts are preferred for LED phosphors over oxide hosts, since only the ionic nature of fluorides results in a sufficiently small nephelauxetic effect, maintaining the energy of the emitting 2 E g → 4 A 2g transition within the visible part of the spectrum, corresponding to red emission with a zero phonon line in the 617-624 nm range. 8,9 For instance in the oxide phosphors, GdAlO 3 :Mn 4+ , SrTiO 3 :Mn 4+ and Y 2 Sn 2 O 7 :Mn 4+ the emission is well beyond 650 nm and thus unsuitable for visible displays or lighting. [10][11][12] The interest in K 2 SiF 6 :Mn 4+ as a red phosphor started with the development of a synthesis method by Adachi and Takahashi, etching Si wafers in HF in the presence of KMnO 4 .…”
mentioning
confidence: 99%
“…More details about this remarkable feature of these two energy levels can be found in recent publications. 20,21 It is obvious that if Dq = 0, we recover the energy level scheme of a free ion. With increasing Dq we see how the energy levels are split and how they behave.…”
Section: Electronic Properties Of Ions With D 3 Electron Configuratiomentioning
confidence: 99%